"A Great School Benefits Us All": Advantaged Parents and the Gentrification of an Urban Public School. (October 2019) - Freidus, Alexandra
Middle-class, professional, and White families in gentrifying cities are increasingly choosing neighborhood public schools. As critical consumers of public education, these families frequently bring not only new resources to schools but also new demands. This article examines the process of "school gentrification" by analyzing the discourse of a neighborhood parents' listserv. I find that as they worked to make their local public school "great, " advantaged parents performed the role of careful investors, defined themselves as the source of the school's potential value, and marginalized low-income families and families of color. These findings raise important questions about educational equity for both educational researchers and urban school and district leaders.